2016
DOI: 10.1039/c6dt01200k
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interaction of U(vi) with phosphonate-functionalized mesoporous silica using solid-state NMR spectroscopy

Abstract: The fundamental interaction of U(vi) with diethylphosphatoethyl triethoxysilane functionalized SBA-15 mesoporous silica is studied by macroscopic batch experiments and solid-state NMR spectroscopy. DPTS-functionalized silica has been shown to extract U(vi) from nitric acid solutions at or above pH 3. Extraction is dependent on pH and ionic strength. Single-pulse (31)P NMR on U(vi) contacted samples revealed that U(vi) only interacts with a fraction of the ligands present on the surface. At pH 4 the U(vi) extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Similar 1-3 nm decreases in average pore diameter have been observed in other silica materials after modification with an organic monolayer. 21,43,44 While the nitrogen adsorption isotherms of AcPhos-SBA 1and 2are both type IV with H 1 hysteresis loops, the shapes of the isotherms for AcPhos-SBA (3) and (4) look different. The isotherm and hysteresis loop for AcPhos-SBA (3) appear to be type IV-H 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar 1-3 nm decreases in average pore diameter have been observed in other silica materials after modification with an organic monolayer. 21,43,44 While the nitrogen adsorption isotherms of AcPhos-SBA 1and 2are both type IV with H 1 hysteresis loops, the shapes of the isotherms for AcPhos-SBA (3) and (4) look different. The isotherm and hysteresis loop for AcPhos-SBA (3) appear to be type IV-H 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The U(VI) sorption isotherm for AcPhos-SBA (2) was not described particularly well by either the Langmuir or Freundlich models, which is evidence that a more complex sorption environment exists between uranyl cations and AcPhos-SBA (2). In our previous work, 21 we observed that the sorption of U(VI) on diethylphosphonate (DPTS)-functionalized SBA-15 from pH 4 nitric acid solutions was described slightly better by the Freundlich model than the Langmuir model. Combined with evidence from NMR spectroscopy, observation of the Freundlich sorption isotherm led us to believe that the uranyl ions were complexed to both ligands and surface silanols.…”
Section: Influence Of Functionalization Procedures On U(vi) Sorptionmentioning
confidence: 95%
See 3 more Smart Citations